SWOT Analysis in Quality Improvement Planning in Integrated Islamic Elementary Schools - Yulita Suyatmika; Mesiono Mesiono; Fachruddin Azmi; Budi Setiawan Ginting; Rija Ansyari (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze SWOT in quality improvement planning at the integrated Islamic elementary school Ad-Durrah Medan. This study uses a qualitative approach with a descriptive study method. Data collection was carried out systematically, starting from observations, interviews with informants, and document studies. Data analysis uses reduction techniques (data sorting), data presentation, and conclusion drawing. Finally, the validity of the study was tested through the persistence of observations and triangulation of data. The results of this study concluded that the quality improvement plan at SDIT Ad-Durrah Medan was well implemented, including the tahfiz al-Qur'an program, strengthening character education, adding extracurricular activities, and strengthening Islamic personal development programs. This is characterized by 4 aspects, namely (1) strengths, including strategic school locations, adequate learning facilities, competent school human resources, conducive and beautiful school climate, and assessment standards that involve (coordination) with parents/guardians of students; (2) weakness, in the form of an unaccredited school; (3) opportunities, including; potential (talents) of students, support from parents/guardians, academic and non-academic achievements of students at the city and provincial levels, as well as harmonious relations between the school and the surrounding community; (4) threats, critical attitude of students' guardians towards children's development, so that teachers must be wiser in leading learning, making decisions and giving exemplary attitudes.